Labour market institutions around the world - Freeman, Richard Barry (London, 2008)
"This paper documents the large cross-country differences in labor institutions that make them a candidate explanatory factor for the divergent economic performance of countries and reviews what economists have learned about the effects of these institutions on economic outcomes. It identifies three ways in which institutions affect economic performance: by altering incentives, by facilitating efficient bargaining, and by increasing information, communication, and trust. The evidence shows that labor institutions reduce the dispersion of earnings and income inequality, which alters incentives, but finds equivocal effects on other aggregate outcomes, such as employment and unemployment. Given weaknesses in the crosscountry data on which most studies focus, the paper argues for increased use of micro-data, simulations, and experiments to illuminate how labor institutions operate and affect outcomes. "